Travel behaviour of the park and ride users and the factors influencing the demand for the use of the park and ride facility - Mohamad, J. (2008)
Park and ride scheme acts as an important component of the parking management strategies of a city. Exploring the significant attributes that influence the utilization of such scheme can provide a better understanding of its application among the urban users. The three main areas of concern towards understanding the characteristics of the park and ride users are the socioeconomic, trip and the parking-related characteristics. Through linear regression, this study identified that the significant attributes that were found to significantly influence the utilization of the facility in the Kuala Lumpur conurbation are total travel time by rail (via the park-and-ride), income, trip purpose, egress mode and types of rail ticket used.